Making and unmaking state-centered capitalism in Serbia - Lazić, Mladen; Pešić, jelena (Beograd : Institute of Sociology and Social Research, Faculty of Philosophy, University : Čigoja štampa, 2021)
Sažetak.
Bibliografija: str. 137-143 i bibliografske bilješke uz tekst
Keywords: kapitalizam - Srbija -- tranzicija - Srbija -- tržišno gospodarstvo - Srbija